Explainable AI based neurofeedback in a CNN-BCI for motor imagery classification - Ghosh, Amitrajit (Nanyang Technological University, 2024)
The application of machine learning to brain-computer interfaces has recently garnered great interest due to the significant advancements in the areas of neural networks and deep learning. With the use of state-of-the-art convolutional neural networks, it has become possible to achieve accuracies of up to 84.19% for subject-independent left/right motor-imagery models using deep convolutional neural networks.